Archiving & preservation of Information Initiatives at Raman Research Institute (RRI) - Benegal, Vrinda J. (Journal of Information and Knowledge, 2014)
In the present electronic era, knowledge generation is mostly depend on the Internet. Knowledge is said to be doubling every two years and hence the preservation of scholarly information has become an important function for the libraries. This has opened up a new avenue for digital preservation and its access. The information landscape is moving rapidly from paper/print to electronic, where it becomes important to store the digital information for posterity. Ever changing technology and electronic storage media is a concern for conservation, maintenance and preservation of digitized collection of scientific literature. This paper provides a varied account of how archiving and digital preservation of information was done and furthermore an effort is being made to display RRI digital collections, archiving and preservation for larger use.